Predominio del"cerebro triádico" de acuerdo a niveles de desempeño estratégico de un grupo de trabajadores colombianos (2018)
Introduction: Organizations have valid tools that help recognize neurotalents, providing elements for staff recruitment and strategic development. Objective: To assess cerebral predominance in a group of workers according to their level of strategic performance, based on the theory of the "triadic brain." Methods: Descriptive-evaluative, multicentric study, with a quantitative approach and a non-experimental design, carried out with a sample of 68 workers from the cities of Sincelejo and Rioacha, who were selected in a non-probabilistic way and who perform activities at different strategic levels. Data collection was done by means of the revealing test for the triadic mental quotient designed by Waldemar De Gregory, while the analysis was carried out by descriptive statisticians. Results: The majority of the workers belong to the female sex (60%), they perform missionary positions (73.8%), and they have predominance of central brain (46.0%), a scale of superior measurement. Conclusions: The predominance of triadic brain corresponds to the central brain with a higher level and development of strategic missionary level activities. © 2018 Revista Cubana de Enfermería.